Laporan Kasus : Frenektomi dengan Electrosurgery - Rahmidian Safitri (Fakultas Kedokteran Gigi Universitas Jember, 2023)
The frenulum is a fold of mucous membrane that attaches the lips and cheeks to the alveolar mucosa, gingiva, and underlying periosteum. High frenulum attachment can cause periodontal and esthetic problems, such as gingivitis, gingival recession, and central diastema which require frenectomy. Frenectomy is the complete removal of the frenulum, including its attachment to the alveolar bone, causing a wide wound and triggering bleeding. A 21-year-old female patient who came to the Mataram City Hospital complained that her upper front teeth were not meeting and spaced. This situation makes the patient feel insecure. The patient had no history of systemic disease. OHIS is good and objective examination shows a central diastema due to the attachment of the superior labial frenum which achieves papillary penetration. Management is done by frenectomy with electrosurgery. The patient was very satisfied with the results. Frenectomy using electrosurgery provides good esthetic results and less bleeding.